Ventilatory and Near-Infrared Spectroscopy Responses Similarly Determine Anaerobic Threshold in Patients With Heart Failure. Issue 2 (March 2020) - Reis, Michel Silva; Nasser, Igor; Barroco, Adriano; Berton, Danilo Cortozi; Neder, José Alberto; Arena, Ross; Borghi-Silva, Audrey
Abstract : Purpose: The present study compared the level of agreement of anaerobic threshold (AT) between ventilatory and near-infrared spectroscopy (NIRS) techniques in patients with chronic heart failure (CHF) and healthy subjects. Methods: Patients with CHF (n = 9) and a control group (CG; n = 14) underwent cardiopulmonary exercise testing on a cycle ergometer until physical exhaustion. Determination of AT was performed visually by (1) ventilatory-expired gas analysis curves and (2) oxyhemoglobin (O2 Hb) and deoxyhemoglobin (HHb) curves assessed by NIRS. Results: The CHF group presented significantly lower oxygen consumption (O2 ), heart rate, and workload at AT when compared with the CG measured by NIRS ( P < .05). However, the effect size, measured by the Cohen d, revealed large magnitude (>0.80) in both techniques when compared between CHF patients and the CG. In addition, ventilatory and NIRS techniques demonstrated significant and very strong/strong correlations for relative O2 ( r = 0.91) and heart rate ( r = 0.85) in the detection of AT in the CHF group. Conclusion: Both ventilatory and NIRS assessments are correlated and there are no differences in the responses between CHF patients and healthy subjects in the determination of AT. These findings indicate both approaches may have utility in the assessment of submaximal exercise performance in patients with CHF. Abstract : Supplemental Digital Content is Available in the Text.Cardiopulmonary exercise testing provides an assessment of cardiorespiratory fitness, and near-infrared spectroscopy adds information related to the skeletal muscle response. The determination of anaerobic threshold using visual methods of both is correlated in heart failure patients and healthy subjects. Using these strategies, it is possible to assess central and peripheral mechanisms.